Analysis of Fosfor Hara Elements in Coconut Leaves Oil By Spectrofotometry - Rudi Munzirwan Siregar (Universitas Negeri Medan, 2020)
As Have been conducted by analysis element of hara phosphorus at palm leaf in indonesia oil palm research institute at medan. Determination of phosphorus rate in palm leaf conducted with methode of spektrofotometri uv-visible. Result of analysis indicate that phosphorus rate the obtained is 0,16% in palm leaf. Of this result indicate that phosphorus rate in palm leaf still less, answer the demand of standard which have been determined by that is between 0,17 - 0,19%.